A Co(II), Zn(II) bimetallic doped carbon material and its preparation method and application

By using the Chitosan decayed carbon material doped with Co(II) and Zn(II) bimetallic doped as a catalyst, synergistically catalyzed oxidation of cycloalkanes, the problems of high reaction temperature and poor selectivity in the prior art were solved, and efficient and selective catalytic oxidation of cycloalkanes were achieved.

CN113649013BActive Publication Date: 2025-04-01ZHEJIANG UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111017678.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-08-31
Publication Date
2025-04-01
Estimated Expiration
2041-08-31

AI Technical Summary

Technical Problem

The prior art has high reaction temperature, low substrate conversion rate, poor selectivity of target products when catalyzed oxidation of cycloalkanes, and difficult to suppress the formation of aliphatic diacids.

Method used

The non-selective thermal decomposition of the oxidation of cycloalkanes by using Co(II) and Zn(II) bimetal doped chitosan-derived carbon materials as catalysts are used to synergistically catalyze the oxidation of cycloalkanes, and the non-selective thermal decomposition of the oxidized intermediate product cycloalkyl hydrogen peroxide is inhibited.

Benefits of technology

The selectivity of catalytic oxidation of cycloalkanes is improved, the reaction temperature is reduced, the generation of by-products is reduced, and the content of cycloalkyl hydroperoxide is low and the safety factor is high.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

A Co(II) and Zn(II) bimetallic doped carbon material is prepared by the following method: chitosan is dispersed in a mixed aqueous solution of a Co(II) element donor and a Zn(II) element donor, metal ions are loaded by stirring at 0-80°C for 1-20 hours, then filtered, washed with water, dried, carbonized at 100-800°C in a N2 atmosphere for 1-10 hours, cooled to room temperature, stirred and washed with a 0.5-10 mol / L hydrochloric acid aqueous solution for 1-10 hours, filtered, washed with water until the pH value is 3-8, and vacuum dried to obtain the material. The material is simple to prepare, low in cost, and easy to industrially apply. The method for synthesizing cycloalkyl alcohol and cycloalkyl ketone by synergistic catalytic oxidation of cycloalkane using the obtained catalytic material has the advantages of high selectivity of cycloalkyl alcohol and cycloalkyl ketone, low reaction temperature, few by-products, small environmental impact, and low cycloalkyl hydroperoxide content and high safety factor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a Co(II) and Zn(II) bimetallic doped carbon material and a preparation method thereof and application thereof in catalytic oxidation of cycloalkanes to synthesize cycloalkanols and cycloalkanones, belonging to the field of industrial catalysis and fine organic synthesis. Background Art

[0002] The catalytic oxidation of cycloalkanes is a very important transformation process in the chemical industry. Its oxidation products, cycloalkanols and cycloalkanones, are not only important organic solvents, but also important fine chemical intermediates. They are widely used in the synthesis of fine chemical products such as pesticides, medicines, dyes, surfactants, resins, etc., especially in the production of polyamide fibers nylon-6 and nylon-66.

[0003] At present, the catalytic oxidation of cycloalkanes in industry is mainly based on homogeneous Co 2+ or Mn 2+ The main problems of the reaction are high reaction temperature, low substrate conversion rate, poor selectivity of target products, and especially the difficulty in inhibiting the formation of aliphatic diacids (Applied Catalysis A, General 2019, 575: 120-131; Catalysis Communications 2019, 132: 105809). The main causes of the above problems are:

[0004] (1) Currently, industrial O2 oxidation of cycloalkanes mainly undergoes a disordered free radical diffusion process;

[0005] (2) The oxidation intermediates, cycloalkyl hydroperoxides, are converted into the target oxidation products, cycloalkanols and cycloalkanones, by a free radical thermal decomposition pathway, which increases the uncontrollability of the reaction system and reduces the selectivity of cycloalkyl alcohols and cycloalkyl ketones.

[0006] Therefore, effectively controlling the diffusion of free radicals in the O2-catalyzed oxidation of cycloalkanes and catalytically converting the oxidation intermediate cycloalkyl hydroperoxide will be beneficial to improving the selectivity of catalytic oxidation of cycloalkanes, and will be a very novel and highly significant process improvement in the field of industrial catalytic oxidation of cycloalkanes.

[0007] Chitosan is the product of chitin deacetylation. It is the only alkaline amino polysaccharide that exists in large quantities in natural polysaccharides. It is rich in sources, highly renewable, non-toxic and harmless, and has extensive and important application value in agriculture and food. After dissolution, chitosan is in a gel-like state. It is an excellent carrier material with strong stability and adsorption. It can effectively chelate divalent metal ions, has strong stability, and achieves efficient dispersion of catalytic active centers. It can also provide a certain microscopic confined environment for chemical reactions and improve reaction selectivity (Ma Huijie, Li Hao, Li Fang, Zhang Yaopeng, Shen Chensi. Preparation of chitosan-loaded magnetic nano zero-valent copper and its catalytic reduction activity [J]. Chemical Industry and Environmental Protection, 2021, 41(03): 342-349). The preparation of carbon materials by carbonization with chitosan as a precursor can well retain the porous structure of chitosan and form a catalytic active center carrier with a high specific surface area. In addition, Zn(II) can catalyze the decomposition and transformation of cycloalkane oxidation intermediates cycloalkyl hydroperoxides, prevent their non-selective thermal decomposition and transformation, and improve the selectivity of cycloalkane catalytic oxidation (Catalysis Communications 2019, 132: 105809).

[0008] Therefore, the present invention uses Co(II) and Zn(II) bimetallic doped chitosan-derived carbon materials as catalysts to catalyze the O2 oxidation of cycloalkanes to selectively synthesize cycloalkyl alcohols and cycloalkyl ketones. The method not only has the advantages of high selectivity for cycloalkyl alcohols and cycloalkyl ketones, low reaction temperature, few by-products, and small environmental impact, but also the method provided by the present invention has low cycloalkyl hydroperoxide content and high safety factor. The method is an efficient, feasible and safe method for selective catalytic oxidation of cycloalkanes to synthesize cycloalkyl alcohols and cycloalkyl ketones. Summary of the invention

[0009] The object of the present invention is to provide a Co(II) and Zn(II) bimetallic doped carbon material and a preparation method thereof and application thereof in catalytic oxidation of cycloalkanes to synthesize cycloalkyl alcohols and cycloalkyl ketones.

[0010] The technical solution of the present invention is as follows:

[0011] A Co(II) and Zn(II) bimetallic doped carbon material is prepared by the following method:

[0012] The chitosan is dispersed in a mixed aqueous solution of a Co(II) element donor and a Zn(II) element donor, and the metal ions are loaded by stirring at 0-80°C for 1-20 hours, and then filtered, washed with water, dried, carbonized at 100-800°C for 1-10 hours under a N2 atmosphere, cooled to room temperature (20-30°C), and stirred and washed with a 0.5-10 mol / L hydrochloric acid aqueous solution for 1-10 hours, filtered, washed with water until the pH value is 3-8, and vacuum dried to obtain a Co(II) and Zn(II) bimetallic doped carbon material;

[0013] The Co(II) element donor is one or a mixture of any proportion of Co(CH3COO)2, Co(NO2)2, CoSO4, CoCl2 and hydrates thereof, preferably anhydrous Co(CH3COO)2;

[0014] The Zn(II) element donor is one or a mixture of any proportion of Zn(CH3COO)2, Zn(NO2)2, ZnSO4, ZnCl2 and hydrates thereof, preferably anhydrous Zn(CH3COO)2;

[0015] The ratio of the amount of glucosamine units in the chitosan to the total amount of Co(II) and Zn(II) is 4:0.1-2, preferably 4:1;

[0016] The molar ratio of the Co(II) to Zn(II) substances is 1:0.1-2, preferably 1:0.5-1.5;

[0017] The stirring time for loading metal ions is preferably 5 to 15 hours;

[0018] The carbonization temperature is preferably 400-800°C, and the time is preferably 1-5 hours.

[0019] The concentration of the hydrochloric acid aqueous solution is preferably 0.5 to 5 mol / L.

[0020] The Co(II) and Zn(II) bimetallic doped carbon material prepared by the present invention can be used in the reaction of catalytic oxidation of cycloalkanes to synthesize cycloalkanols and cycloalkanones. The specific application method is:

[0021] The Co(II) and Zn(II) bimetallic doped carbon materials are dispersed in cycloalkane, the reaction system is sealed, the temperature is raised to 80-160°C under stirring, an oxidant is introduced to 0.1-2MPa, the set temperature and pressure are maintained, the reaction is stirred for 2-24h, and the reaction solution is then post-treated to obtain oxidation products cycloalkyl alcohol and cycloalkyl ketone;

[0022] The cycloalkane is one or a mixture of any proportion of two or more of cyclopentane, cyclohexane, cycloheptane, cyclooctane, cyclononane, cyclodecane and cyclododecane;

[0023] The mass amount of the Co(II) and Zn(II) bimetallic doped carbon material is 0.01 to 10 g / 100 mol, preferably 0.5 to 10 g / 100 mol, calculated as the amount of cycloalkane;

[0024] The preferred reaction temperature is 100-130°C, and the preferred reaction pressure is 0.6-1.2 MPa;

[0025] The stirring rate is 600-1200 rpm, preferably 800-1000 rpm;

[0026] The oxidant is oxygen, air or a mixture of the two in any proportion;

[0027] The post-treatment method is as follows: after the reaction is completed, triphenylphosphine (PPh3, the amount used is 3% of the amount of cycloalkane substance) is added to the reaction solution, stirred at room temperature for 40 minutes (to reduce the generated peroxide), and the crude product is distilled, vacuum distilled and recrystallized to obtain an oxidation product;

[0028] The analysis method for the reaction results is as follows: after the reaction is completed, the reaction liquid is reduced with triphenylphosphine to generate peroxide, and then sampled for analysis, diluted with acetone as a solvent, and toluene as an internal standard, and gas chromatography analysis is performed to calculate the conversion rate of cycloalkanes, the selectivity of cycloalkyl alcohols, cycloalkyl ketones and peroxides; liquid chromatography analysis is performed with benzoic acid as an internal standard to calculate the selectivity of aliphatic diacids.

[0029] The beneficial effects of the present invention are mainly reflected in:

[0030] The present invention constructs a bimetallic catalytic system with Co(II) and Zn(II) bimetallic doped carbon materials, and synergistically catalyzes the oxidation of cycloalkanes by O2 to synthesize cycloalkyl alcohols and cycloalkyl ketones, which not only effectively inhibits the disordered diffusion of free radicals in the oxidation process, but also realizes the catalytic conversion of the oxidation intermediate cycloalkyl hydroperoxide, greatly improves the selectivity of the target products cycloalkyl alcohols and cycloalkyl ketones, reduces the generation of by-products, and reduces the emission of environmental pollutants, which meets the current chemical industry's practical needs for "energy conservation and emission reduction". The present invention not only provides an efficient bimetallic catalytic material, but also provides a method for efficiently and selectively oxidizing the CH bonds of cycloalkanes to synthesize cycloalkyl alcohols and cycloalkyl ketones, and has a certain reference value for the selective catalytic oxidation of the CH bonds of other hydrocarbons and the efficient preparation of alcohols and ketone compounds.

[0031] The Co(II) and Zn(II) bimetallic doped carbon material of the present invention is simple to prepare, low in cost, and easy to apply industrially. The method for synthesizing cycloalkyl alcohols and cycloalkyl ketones by synergistic catalytic oxidation of cycloalkanes by the obtained catalytic material has the advantages of high selectivity of cycloalkyl alcohols and cycloalkyl ketones, low reaction temperature, few by-products, and small environmental impact. In addition, the cycloalkyl hydroperoxide content of the present invention is low and the safety factor is high. The present invention provides an efficient, feasible, and safe method for synthesizing cycloalkyl alcohols and cycloalkyl ketones by selective catalytic oxidation of cycloalkanes. DETAILED DESCRIPTION

[0032] The present invention is further described below by means of specific embodiments, but the protection scope of the present invention is not limited thereto.

[0033] Examples 1 to 18 are the synthesis of Co(II) and Zn(II) bimetallic doped carbon materials.

[0034] Examples 19 to 53 are examples of catalytic oxidation of cycloalkanes.

[0035] Examples 54 to 57 are comparative experiments.

[0036] Example 58 is an enlarged experiment.

[0037] Example 1

[0038] Take 2.2128g (12.50mmol) of anhydrous cobalt acetate and 2.2935g (12.50mmol) of anhydrous zinc acetate and dissolve them in 250mL of deionized water. Stir on a magnetic stirrer for 15min. After the salt is completely dissolved, add 16.1180g of chitosan (the amount of aminoglucose unit substance is 100mmol) and stir on a magnetic stirrer for 6.0h. After standing for 30min, vacuum filter and wash 3 times with 3×100mL of water until the filtrate is clear. Dry in the shade at room temperature for 24.0h and then vacuum dry at 80℃. Carbonize at 700℃ for 2.0h under N2 atmosphere. The obtained carbon material is dispersed in 50.0mL of dilute hydrochloric acid (2.0mol / L), stirred and washed for 6.0h, and then vacuum filtered. Rinse with 2×50mL of deionized water until the pH value is 5.0-6.0, and vacuum dry to obtain 12.1842g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50 -700-2.0 (the molar ratio of glucosamine unit, Co, and Zn is 8:1:1, 700 is the carbonization temperature, and 2.0 is the carbonization time).

[0039] Example 2

[0040] Take 2.9509g (16.67mmol) of anhydrous cobalt acetate and 1.5284g (8.33mmol) of anhydrous zinc acetate and dissolve them in 250mL of deionized water. Stir on a magnetic stirrer for 15min. After the salt is completely dissolved, add 16.1180g of chitosan (the amount of aminoglucose unit substance is 100mmol) and stir on a magnetic stirrer for 6.0h. After standing for 30min, filter under reduced pressure, wash 3 times with 3×100mL of water until the filtrate is clear, dry in the shade at room temperature for 24.0h, and then vacuum dry at 80℃. Carbonize at 700℃ for 2.0h under N2 atmosphere. The obtained carbon material is dispersed in 50.0mL of dilute hydrochloric acid (2.0mol / L), stirred and washed for 6.0h, and then filtered under reduced pressure. It is rinsed with 2×50mL of deionized water until the pH value is 5.0-6.0, and vacuum dried to obtain 13.2413g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.67:0.33-700-2.0 (the molar ratio of glucosamine unit, Co, and Zn is 4:0.67:0.33, 700 is the carbonization temperature, and 2.0 is the carbonization time).

[0041] Example 3

[0042] Take 1.7702g (10.00mmol) of anhydrous cobalt acetate and 2.7522g (15.00mmol) of anhydrous zinc acetate and dissolve them in 250mL of deionized water. Stir on a magnetic stirrer for 15min. After the salt is completely dissolved, add 16.1180g of chitosan (the amount of aminoglucose unit substance is 100mmol) and stir on a magnetic stirrer for 6.0h. After standing for 30min, filter under reduced pressure, wash 3 times with 3×100mL of water until the filtrate is clear, dry in the shade at room temperature for 24.0h, and then vacuum dry at 80℃. Carbonize at 700℃ for 2.0h under N2 atmosphere. The obtained carbon material is dispersed in 50.0mL of dilute hydrochloric acid (2.0mol / L), stirred and washed for 6.0h, and then filtered under reduced pressure. It is rinsed with 2×50mL of deionized water until the pH value is 5.0-6.0, and vacuum dried to obtain 12.8795g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.40:0.60 -700-2.0 (the molar ratio of glucosamine unit, Co, and Zn is 4:0.40:0.60, 700 is the carbonization temperature, and 2.0 is the carbonization time).

[0043] Example 4

[0044] Take 2.2128g (12.50mmol) of anhydrous cobalt acetate and 2.2935g (12.50mmol) of anhydrous zinc acetate and dissolve them in 250mL of deionized water. Stir on a magnetic stirrer for 15min. After the salt is completely dissolved, add 16.1180g of chitosan (the amount of aminoglucose unit substance is 100mmol) and stir on a magnetic stirrer for 6.0h. After standing for 30min, filter under reduced pressure, wash 3 times with 3×100mL of water until the filtrate is clear, dry in the shade at room temperature for 24.0h, and then vacuum dry at 80℃. Carbonize at 400℃ for 2.0h under N2 atmosphere. The obtained carbon material is dispersed in 50.0mL of dilute hydrochloric acid (1.0mol / L), stirred and washed for 6.0h, and then filtered under reduced pressure. It is rinsed with 2×50mL of deionized water until the pH value is 5.0-6.0, and vacuum dried to obtain 16.2814g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50 -400-2.0 (the molar ratio of glucosamine unit, Co, and Zn is 4:0.50:0.50, 400 is the carbonization temperature, and 2.0 is the carbonization time).

[0045] Example 5

[0046] Take 2.9509g (16.67mmol) of anhydrous cobalt acetate and 1.5284g (8.33mmol) of anhydrous zinc acetate and dissolve them in 250mL of deionized water. Stir on a magnetic stirrer for 15min. After the salt is completely dissolved, add 16.1180g of chitosan (the amount of aminoglucose unit substance is 100mmol) and stir on a magnetic stirrer for 6.0h. After standing for 30min, filter under reduced pressure, wash 3 times with 3×100mL of water until the filtrate is clear, dry in the shade at room temperature for 24.0h, and then vacuum dry at 80℃. Carbonize at 400℃ for 2.0h under N2 atmosphere. The obtained carbon material is dispersed in 50.0mL of dilute hydrochloric acid (1.0mol / L), stirred and washed for 6.0h, and then filtered under reduced pressure. It is rinsed with 2×50mL of deionized water until the pH value is 5.0-6.0, and vacuum dried to obtain 15.7852g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.67:0.33 -400-2.0 (the molar ratio of glucosamine unit, Co, and Zn is 4:0.67:0.33, 400 is the carbonization temperature, and 2.0 is the carbonization time).

[0047] Example 6

[0048] Take 1.7702g (10.00mmol) of anhydrous cobalt acetate and 2.7522g (15.00mmol) of anhydrous zinc acetate and dissolve them in 250mL of deionized water. Stir on a magnetic stirrer for 15min. After the salt is completely dissolved, add 16.1180g of chitosan (the amount of aminoglucose unit substance is 100mmol) and stir on a magnetic stirrer for 6.0h. After standing for 30min, filter under reduced pressure, wash 3 times with 3×100mL of water until the filtrate is clear, dry in the shade at room temperature for 24.0h, and then vacuum dry at 80℃. Carbonize at 400℃ for 2.0h under N2 atmosphere. The obtained carbon material is dispersed in 50.0mL of dilute hydrochloric acid (1.0mol / L), stirred and washed for 6.0h, and then filtered under reduced pressure. It is rinsed with 2×50mL of deionized water until the pH value is 5.0-6.0, and vacuum dried to obtain 15.8762g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.40:0.60 -400-2.0 (the molar ratio of glucosamine unit, Co, and Zn is 4:0.40:0.60, 400 is the carbonization temperature, and 2.0 is the carbonization time).

[0049] Example 7

[0050] Take 2.2128g (12.5mmol) of anhydrous cobalt acetate and 2.2935g (12.5mmol) of anhydrous zinc acetate and dissolve them in 250mL of deionized water. Stir on a magnetic stirrer for 15min. After the salt is completely dissolved, add 16.1180g of chitosan (the amount of glucosamine unit substance is 100mmol) and stir on a magnetic stirrer for 6.0h. After standing for 30min, filter under reduced pressure, wash 3 times with 3×100mL of water until the filtrate is clear, dry in the shade at room temperature for 24.0h, and then vacuum dry at 80℃. Carbonize at 600℃ for 2.0h under N2 atmosphere. The obtained carbon material is dispersed in 50.0mL of dilute hydrochloric acid (3.0mol / L), stirred and washed for 6.0h, and then filtered under reduced pressure. It is rinsed with 2×50mL of deionized water until the pH value is 5.0-6.0, and vacuum dried to obtain 14.4215g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50 -600-2.0 (the molar ratio of glucosamine unit, Co, and Zn is 4:0.50:0.50, 600 is the carbonization temperature, and 2.0 is the carbonization time).

[0051] Example 8

[0052] Take 2.9509g (16.67mmol) of anhydrous cobalt acetate and 1.5284g (8.33mmol) of anhydrous zinc acetate and dissolve them in 250mL of deionized water. Stir on a magnetic stirrer for 15min. After the salt is completely dissolved, add 16.1180g of chitosan (the amount of aminoglucose unit substance is 100mmol) and stir on a magnetic stirrer for 6.0h. After standing for 30min, vacuum filter and wash 3 times with 3×100mL of water until the filtrate is clear. Dry in the shade at room temperature for 24.0h and then vacuum dry at 80℃. Carbonize at 600℃ for 2.0h under N2 atmosphere. The obtained carbon material is dispersed in 50.0mL of dilute hydrochloric acid (3.0mol / L), stirred and washed for 6.0h, and then vacuum filtered. Rinse with 2×50mL of deionized water until the pH value is 5.0-6.0, and vacuum dry to obtain 14.6427g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.67:0.33 -600-2.0 (the molar ratio of glucosamine unit, Co, and Zn is 4:0.67:0.33, 600 is the carbonization temperature, and 2.0 is the carbonization time).

[0053] Example 9

[0054] Take 1.7702g (10.00mmol) of anhydrous cobalt acetate and 2.7522g (15.00mmol) of anhydrous zinc acetate and dissolve them in 250mL of deionized water. Stir on a magnetic stirrer for 15min. After the salt is completely dissolved, add 16.1180g of chitosan (the amount of aminoglucose unit substance is 100mmol) and stir on a magnetic stirrer for 6.0h. After standing for 30min, filter under reduced pressure, wash 3 times with 3×100mL of water until the filtrate is clear, dry in the shade at room temperature for 24.0h, and then vacuum dry at 80℃. Carbonize at 600℃ for 2.0h under N2 atmosphere. The obtained carbon material is dispersed in 50.0mL of dilute hydrochloric acid (3.0mol / L), stirred and washed for 6.0h, and then filtered under reduced pressure. It is rinsed with 2×50mL of deionized water until the pH value is 5.0-6.0, and vacuum dried to obtain 14.1871g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.40:0.60 -600-2.0 (the molar ratio of glucosamine unit, Co, and Zn is 4:0.40:0.60, 600 is the carbonization temperature, and 2.0 is the carbonization time).

[0055] Example 10

[0056] Take 2.2128g (12.5mmol) of anhydrous cobalt acetate and 2.2935g (12.5mmol) of anhydrous zinc acetate and dissolve them in 250mL of deionized water. Stir on a magnetic stirrer for 15min. After the salt is completely dissolved, add 16.1180g of chitosan (the amount of glucosamine unit substance is 100mmol) and stir on a magnetic stirrer for 6.0h. After standing for 30min, filter under reduced pressure, wash 3 times with 3×100mL of water until the filtrate is clear, dry in the shade at room temperature for 24.0h, and then vacuum dry at 80℃. Carbonize at 800℃ for 2.0h under N2 atmosphere. The obtained carbon material is dispersed in 50.0mL of dilute hydrochloric acid (4.0mol / L), stirred and washed for 6.0h, and then filtered under reduced pressure. It is rinsed with 2×50mL of deionized water until the pH value is 5.0-6.0, and vacuum dried to obtain 10.2845g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50 -800-2.0 (the molar ratio of glucosamine unit, Co, and Zn is 4:0.50:0.50, 800 is the carbonization temperature, and 2.0 is the carbonization time).

[0057] Embodiment 11

[0058] Take 2.9509g (16.67mmol) of anhydrous cobalt acetate and 1.5284g (8.33mmol) of anhydrous zinc acetate and dissolve them in 250mL of deionized water. Stir on a magnetic stirrer for 15min. After the salt is completely dissolved, add 16.1180g of chitosan (the amount of aminoglucose unit substance is 100mmol) and stir on a magnetic stirrer for 6.0h. After standing for 30min, filter under reduced pressure, wash 3 times with 3×100mL of water until the filtrate is clear, dry in the shade at room temperature for 24.0h, and then vacuum dry at 80℃. Carbonize at 800℃ for 2.0h under N2 atmosphere. The obtained carbon material is dispersed in 50.0mL of dilute hydrochloric acid (4.0mol / L), stirred and washed for 6.0h, and then filtered under reduced pressure. It is rinsed with 2×50mL of deionized water until the pH value is 5.0-6.0, and vacuum dried to obtain 11.0128g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.67:0.33 -800-2.0 (the molar ratio of glucosamine unit, Co, and Zn is 4:0.67:0.33, 800 is the carbonization temperature, and 2.0 is the carbonization time).

[0059] Example 12

[0060] Take 1.7702g (10.00mmol) of anhydrous cobalt acetate and 2.7522g (15.00mmol) of anhydrous zinc acetate and dissolve them in 250mL of deionized water. Stir on a magnetic stirrer for 15min. After the salt is completely dissolved, add 16.1180g of chitosan (the amount of glucosamine unit substance is 100mmol) and stir on a magnetic stirrer for 6.0h. After standing for 30min, filter under reduced pressure, wash 3 times with 3×100mL of water until the filtrate is clear, dry in the shade at room temperature for 24.0h, and then vacuum dry at 80℃. Carbonize at 800℃ for 2.0h under N2 atmosphere. The obtained carbon material is dispersed in 50.0mL of dilute hydrochloric acid (4.0mol / L), stirred and washed for 6.0h, and then filtered under reduced pressure. It is rinsed with 2×50mL of deionized water until the pH value is 5.0-6.0, and vacuum dried to obtain 10.1358g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.40:0.60 -800-2.0 (the molar ratio of glucosamine unit, Co, and Zn is 4:0.40:0.60, 800 is the carbonization temperature, and 2.0 is the carbonization time).

[0061] Embodiment 13

[0062] Take 2.2128g (12.5mmol) of anhydrous cobalt acetate and 2.2935g (12.5mmol) of anhydrous zinc acetate and dissolve them in 250mL of deionized water. Stir on a magnetic stirrer for 15min. After the salt is completely dissolved, add 16.1180g of chitosan (the amount of aminoglucose unit substance is 100mmol) and stir on a magnetic stirrer for 6.0h. After standing for 30min, filter under reduced pressure, wash 3 times with 3×100mL of water until the filtrate is clear, dry in the shade at room temperature for 24.0h, and then vacuum dry at 80℃. Carbonize at 700℃ for 1.0h under N2 atmosphere. The obtained carbon material is dispersed in 50.0mL of dilute hydrochloric acid (2.0mol / L), stirred and washed for 6.0h, and then filtered under reduced pressure. It is rinsed with 2×50mL of deionized water until the pH value is 5.0-6.0, and vacuum dried to obtain 12.1765g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50 -700-1.0 (the molar ratio of glucosamine unit, Co, and Zn is 4:0.50:0.50, 700 is the carbonization temperature, and 1.0 is the carbonization time).

[0063] Embodiment 14

[0064] Take 2.9509g (16.67mmol) of anhydrous cobalt acetate and 1.5284g (8.33mmol) of anhydrous zinc acetate and dissolve them in 250mL of deionized water. Stir on a magnetic stirrer for 15min. After the salt is completely dissolved, add 16.1180g of chitosan (the amount of aminoglucose unit substance is 100mmol) and stir on a magnetic stirrer for 6.0h. After standing for 30min, filter under reduced pressure, wash 3 times with 3×100mL of water until the filtrate is clear, dry in the shade at room temperature for 24.0h, and then vacuum dry at 80℃. Carbonize at 700℃ for 1.0h under N2 atmosphere. The obtained carbon material is dispersed in 50.0mL of dilute hydrochloric acid (2.0mol / L), stirred and washed for 6.0h, and then filtered under reduced pressure. It is rinsed with 2×50mL of deionized water until the pH value is 5.0-6.0, and vacuum dried to obtain 12.7889g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.67:0.33 -700-1.0 (the molar ratio of glucosamine unit, Co, and Zn is 4:0.67:0.33, 700 is the carbonization temperature, and 1.0 is the carbonization time).

[0065] Embodiment 15

[0066] Take 1.7702g (10.00mmol) of anhydrous cobalt acetate and 2.7522g (15.00mmol) of anhydrous zinc acetate and dissolve them in 250mL of deionized water. Stir on a magnetic stirrer for 15min. After the salt is completely dissolved, add 16.1180g of chitosan (the amount of aminoglucose unit substance is 100mmol) and stir on a magnetic stirrer for 6.0h. After standing for 30min, filter under reduced pressure, wash 3 times with 3×100mL of water until the filtrate is clear, dry in the shade at room temperature for 24.0h, and then vacuum dry at 80℃. Carbonize at 700℃ for 1.0h under N2 atmosphere. The obtained carbon material is dispersed in 50.0mL of dilute hydrochloric acid (2.0mol / L), stirred and washed for 6.0h, and then filtered under reduced pressure. It is rinsed with 2×50mL of deionized water until the pH value is 5.0-6.0, and vacuum dried to obtain 13.3859g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.40:0.60 -700-1.0 (the molar ratio of glucosamine unit, Co, and Zn is 4:0.40:0.60, 700 is the carbonization temperature, and 1.0 is the carbonization time).

[0067] Example 16

[0068] Take 2.2128g (12.5mmol) of anhydrous cobalt acetate and 2.2935g (12.5mmol) of anhydrous zinc acetate and dissolve them in 250mL of deionized water. Stir on a magnetic stirrer for 15min. After the salt is completely dissolved, add 16.1180g of chitosan (the amount of aminoglucose unit substance is 100mmol) and stir on a magnetic stirrer for 6.0h. After standing for 30min, vacuum filter and wash 3 times with 3×100mL of water until the filtrate is clear. Dry in the shade at room temperature for 24.0h and then vacuum dry at 80℃. Carbonize at 700℃ for 3.0h under N2 atmosphere. The obtained carbon material is dispersed in 50.0mL of dilute hydrochloric acid (2.0mol / L), stirred and washed for 6.0h, and then vacuum filtered. Rinse with 2×50mL of deionized water until the pH value is 5.0-6.0, and vacuum dry to obtain 12.1148g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50 -700-3.0 (the molar ratio of glucosamine unit, Co, and Zn is 4:0.50:0.50, 700 is the carbonization temperature, and 3.0 is the carbonization time).

[0069] Embodiment 17

[0070] Take 2.9509g (16.67mmol) of anhydrous cobalt acetate and 1.5284g (8.33mmol) of anhydrous zinc acetate and dissolve them in 250mL of deionized water. Stir on a magnetic stirrer for 15min. After the salt is completely dissolved, add 16.1180g of chitosan (the amount of glucosamine unit substance is 100mmol) and stir on a magnetic stirrer for 6.0h. After standing for 30min, filter under reduced pressure, wash 3 times with 3×100mL of water until the filtrate is clear, dry in the shade at room temperature for 24.0h, and then vacuum dry at 80℃. Carbonize at 700℃ for 3.0h under N2 atmosphere. The obtained carbon material is dispersed in 50.0mL of dilute hydrochloric acid (2.0mol / L), stirred and washed for 6.0h, and then filtered under reduced pressure. It is rinsed with 2×50mL of deionized water until the pH value is 5.0-6.0, and vacuum dried to obtain 11.7832g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.67:0.33 -700-1.0 (the molar ratio of glucosamine unit, Co, and Zn is 4:0.67:0.33, 700 is the carbonization temperature, and 3.0 is the carbonization time).

[0071] Embodiment 18

[0072] Take 1.7702g (10.00mmol) of anhydrous cobalt acetate and 2.7522g (15.00mmol) of anhydrous zinc acetate and dissolve them in 250mL of deionized water. Stir on a magnetic stirrer for 15min. After the salt is completely dissolved, add 16.1180g of chitosan (the amount of aminoglucose unit substance is 100mmol) and stir on a magnetic stirrer for 6.0h. After standing for 30min, filter under reduced pressure, wash 3 times with 3×100mL of water until the filtrate is clear, dry in the shade at room temperature for 24.0h, and then vacuum dry at 80℃. Carbonize at 700℃ for 3.0h under N2 atmosphere. The obtained carbon material is dispersed in 50mL of dilute hydrochloric acid (2.0mol / L), stirred and washed for 6.0h, and then filtered under reduced pressure. It is rinsed with 2×50mL of deionized water until the pH value is 5.0-6.0, and vacuum dried to obtain 12.8795g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.40:0.60 -700-1.0 (the molar ratio of glucosamine unit, Co, and Zn is 4:0.40:0.60, 700 is the carbonization temperature, and 3.0 is the carbonization time).

[0073] Embodiment 19

[0074] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0100 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50-700-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 7.03%, the cyclohexanol selectivity was 44.27%, the cyclohexanone selectivity was 49.72%, the cyclohexyl hydroperoxide selectivity was 2.53%, the adipic acid selectivity was 3.02%, and the glutaric acid selectivity was 0.46%.

[0075] Embodiment 20

[0076] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50 -700-2.0 was dispersed in 14.0280g (200mmol) of cyclopentane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclopentane conversion rate was 5.04%, the cyclopentanol selectivity was 9.45%, the cyclopentanone selectivity was 48.24%, the cyclopentyl hydroperoxide selectivity was 12.06%, the glutaric acid selectivity was 27.62%, and the succinic acid selectivity was 2.63%.

[0077] Embodiment 21

[0078] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50-700-2.0 was dispersed in 19.6380g (200mmol) of cycloheptane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cycloheptane conversion rate was 23.14%, the cycloheptanol selectivity was 9.86%, the cycloheptanone selectivity was 66.59%, the cycloheptyl hydroperoxide selectivity was 20.39%, the pimelic acid selectivity was 2.04%, and the adipic acid selectivity was 1.12%.

[0079] Embodiment 22

[0080] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50 -700-2.0 was dispersed in 22.4440g (200mmol) of cyclooctane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclooctane conversion rate was 27.62%, the cyclooctanol selectivity was 32.41%, the cyclooctanone selectivity was 50.75%, the cyclooctyl hydroperoxide selectivity was 14.56%, the suberic acid selectivity was 1.93%, and the pimelic acid selectivity was 0.35%.

[0081] Embodiment 23

[0082] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50-700-2.0 was dispersed in 33.6640g (200mmol) of cyclododecane, the reactor was sealed, the temperature was raised to 120℃ with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120℃, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide generated was reduced by stirring at room temperature for 30min. Acetone was used as the solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred, and toluene was used as the internal standard for gas chromatography analysis; 10mL of the resulting solution was transferred, and benzoic acid was used as the internal standard for liquid chromatography analysis. The conversion rate of cyclododecane was 30.26%, the selectivity of cyclododecanol was 18.28%, the selectivity of cyclododecanone was 48.37%, the selectivity of cyclododecyl hydroperoxide was 33.35%, and the generation of dodecanoic acid and undecanoic acid was not detected.

[0083] Embodiment 24

[0084] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.67:0.33 -700-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 6.13%, the cyclohexanol selectivity was 43.22%, the cyclohexanone selectivity was 47.76%, the cyclohexyl hydroperoxide selectivity was 2.16%, the adipic acid selectivity was 5.31%, and the glutaric acid selectivity was 1.55%.

[0085] Embodiment 25

[0086] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.40:0.60-700-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 5.85%, the cyclohexanol selectivity was 40.85%, the cyclohexanone selectivity was 45.83%, the cyclohexyl hydroperoxide selectivity was 5.64%, the adipic acid selectivity was 5.67%, and the glutaric acid selectivity was 2.01%.

[0087] Embodiment 26

[0088] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50 -400-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 5.61%, the cyclohexanol selectivity was 42.63%, the cyclohexanone selectivity was 44.65%, the cyclohexyl hydroperoxide selectivity was 3.57%, the adipic acid selectivity was 5.79%, and the glutaric acid selectivity was 3.36%.

[0089] Embodiment 27

[0090] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.67:0.33-400-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 5.32%, the cyclohexanol selectivity was 44.51%, the cyclohexanone selectivity was 45.02%, the cyclohexyl hydroperoxide selectivity was 4.11%, the adipic acid selectivity was 5.12%, and the glutaric acid selectivity was 1.24%.

[0091] Embodiment 28

[0092] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.40:0.60 -400-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 4.89%, the cyclohexanol selectivity was 45.13%, the cyclohexanone selectivity was 45.68%, the cyclohexyl hydroperoxide selectivity was 3.25%, the adipic acid selectivity was 4.95%, and the glutaric acid selectivity was 0.99%.

[0093] Embodiment 29

[0094] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50-600-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 5.77%, the cyclohexanol selectivity was 41.62%, the cyclohexanone selectivity was 47.83%, the cyclohexyl hydroperoxide selectivity was 2.21%, the adipic acid selectivity was 6.75%, and the glutaric acid selectivity was 1.59%.

[0095] Embodiment 30

[0096] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.67:0.33 -600-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 5.02%, the cyclohexanol selectivity was 43.17%, the cyclohexanone selectivity was 48.31%, the cyclohexyl hydroperoxide selectivity was 2.62%, the adipic acid selectivity was 4.12%, and the glutaric acid selectivity was 1.78%.

[0097] Embodiment 31

[0098] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.40:0.60-600-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 4.86%, the cyclohexanol selectivity was 42.58%, the cyclohexanone selectivity was 45.62%, the cyclohexyl hydroperoxide selectivity was 1.73%, the adipic acid selectivity was 7.04%, and the glutaric acid selectivity was 3.03%.

[0099] Embodiment 32

[0100] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50 -800-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 5.71%, the cyclohexanol selectivity was 44.01%, the cyclohexanone selectivity was 42.38%, the cyclohexyl hydroperoxide selectivity was 3.66%, the adipic acid selectivity was 6.78%, and the glutaric acid selectivity was 3.17%.

[0101] Embodiment 33

[0102] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.67:0.33-800-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 5.71%, the cyclohexanol selectivity was 41.85%, the cyclohexanone selectivity was 49.62%, the cyclohexyl hydroperoxide selectivity was 1.05%, the adipic acid selectivity was 6.21%, and the glutaric acid selectivity was 1.27%.

[0103] Embodiment 34

[0104] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.40:0.60 -800-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 4.88%, the cyclohexanol selectivity was 42.58%, the cyclohexanone selectivity was 48.15%, the cyclohexyl hydroperoxide selectivity was 2.16%, the adipic acid selectivity was 5.79%, and the glutaric acid selectivity was 1.32%.

[0105] Embodiment 35

[0106] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50-700-1.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 5.69%, the cyclohexanol selectivity was 42.55%, the cyclohexanone selectivity was 47.61%, the cyclohexyl hydroperoxide selectivity was 3.54%, the adipic acid selectivity was 5.79%, and the glutaric acid selectivity was 0.51%.

[0107] Embodiment 36

[0108] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.67:0.33 -700-1.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 5.33%, the cyclohexanol selectivity was 40.06%, the cyclohexanone selectivity was 50.62%, the cyclohexyl hydroperoxide selectivity was 2.56%, the adipic acid selectivity was 5.21%, and the glutaric acid selectivity was 1.55%.

[0109] Embodiment 37

[0110] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.40:0.60-700-1.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 4.89%, the cyclohexanol selectivity was 40.51%, the cyclohexanone selectivity was 50.02%, the cyclohexyl hydroperoxide selectivity was 1.07%, the adipic acid selectivity was 7.27%, and the glutaric acid selectivity was 1.13%.

[0111] Embodiment 38

[0112] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50 -700-3.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 5.12%, the cyclohexanol selectivity was 43.26%, the cyclohexanone selectivity was 48.46%, the cyclohexyl hydroperoxide selectivity was 2.14%, the adipic acid selectivity was 5.38%, and the glutaric acid selectivity was 0.76%.

[0113] Embodiment 39

[0114] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.67:0.33-700-1.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 4.78%, the cyclohexanol selectivity was 44.17%, the cyclohexanone selectivity was 44.85%, the cyclohexyl hydroperoxide selectivity was 2.18%, the adipic acid selectivity was 7.69%, and the glutaric acid selectivity was 1.11%.

[0115] Embodiment 40

[0116] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.40:0.60 -700-1.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 4.52%, the cyclohexanol selectivity was 39.85%, the cyclohexanone selectivity was 48.67%, the cyclohexyl hydroperoxide selectivity was 3.76%, the adipic acid selectivity was 5.89%, and the glutaric acid selectivity was 1.83%.

[0117] Embodiment 41

[0118] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0050 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50-700-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 5.01%, the cyclohexanol selectivity was 28.56%, the cyclohexanone selectivity was 40.31%, the cyclohexyl hydroperoxide selectivity was 20.67%, the adipic acid selectivity was 6.89%, and the glutaric acid selectivity was 3.57%.

[0119] Embodiment 42

[0120] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0150 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50 -700-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 5.86%, the cyclohexanol selectivity was 33.78%, the cyclohexanone selectivity was 42.51%, the cyclohexyl hydroperoxide selectivity was 14.56%, the adipic acid selectivity was 7.92%, and the glutaric acid selectivity was 1.23%.

[0121] Embodiment 43

[0122] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0200 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50-700-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 5.79%, the cyclohexanol selectivity was 40.89%, the cyclohexanone selectivity was 47.28%, the cyclohexyl hydroperoxide selectivity was 4.59%, the adipic acid selectivity was 6.45%, and the glutaric acid selectivity was 0.79%.

[0123] Embodiment 44

[0124] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0100 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50 -700-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 80°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 4.99%, the cyclohexanol selectivity was 38.42%, the cyclohexanone selectivity was 44.38%, the cyclohexyl hydroperoxide selectivity was 13.50%, the adipic acid selectivity was 2.85%, and the glutaric acid selectivity was 0.85%.

[0125] Embodiment 45

[0126] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0100 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50-700-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 100°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 5.51%, the cyclohexanol selectivity was 41.69%, the cyclohexanone selectivity was 46.52%, the cyclohexyl hydroperoxide selectivity was 7.24%, the adipic acid selectivity was 3.11%, and the glutaric acid selectivity was 1.44%.

[0127] Embodiment 46

[0128] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0100 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50 -700-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 140°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 5.82%, the cyclohexanol selectivity was 41.25%, the cyclohexanone selectivity was 48.12%, the cyclohexyl hydroperoxide selectivity was 2.34%, the adipic acid selectivity was 6.58%, and the glutaric acid selectivity was 1.71%.

[0129] Embodiment 47

[0130] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0100 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50-700-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 0.80MPa. The reaction was stirred at 120°C, 0.80MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 6.38%, the cyclohexanol selectivity was 45.31%, the cyclohexanone selectivity was 47.86%, the cyclohexyl hydroperoxide selectivity was 3.65%, the adipic acid selectivity was 2.33%, and the glutaric acid selectivity was 0.85%.

[0131] Embodiment 48

[0132] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0100 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50 -700-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.20MPa. The reaction was stirred at 120°C, 1.20MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 6.71%, the cyclohexanol selectivity was 44.61%, the cyclohexanone selectivity was 48.74%, the cyclohexyl hydroperoxide selectivity was 2.37%, the adipic acid selectivity was 3.52%, and the glutaric acid selectivity was 0.76%.

[0133] Embodiment 49

[0134] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0100 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50-700-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 4.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 4.83%, the cyclohexanol selectivity was 42.83%, the cyclohexanone selectivity was 46.52%, the cyclohexyl hydroperoxide selectivity was 5.63%, the adipic acid selectivity was 4.08%, and the glutaric acid selectivity was 0.94%.

[0135] Embodiment 50

[0136] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0100 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50 -700-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 6.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 5.06%, the cyclohexanol selectivity was 42.71%, the cyclohexanone selectivity was 46.75%, the cyclohexyl hydroperoxide selectivity was 5.68%, the adipic acid selectivity was 3.85%, and the glutaric acid selectivity was 1.01%.

[0137] Embodiment 51

[0138] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0100 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50-700-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 10.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 5.87%, the cyclohexanol selectivity was 42.58%, the cyclohexanone selectivity was 48.14%, the cyclohexyl hydroperoxide selectivity was 3.58%, the adipic acid selectivity was 4.13%, and the glutaric acid selectivity was 1.57%.

[0139] Embodiment 52

[0140] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0100 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50 -700-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 16.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. Acetone was used as the solvent, and the resulting reaction mixture was fixed to 100mL. 10mL of the resulting solution was transferred and analyzed by gas chromatography with toluene as the internal standard; 10mL of the resulting solution was transferred and analyzed by liquid chromatography with benzoic acid as the internal standard. The cyclohexane conversion rate was 6.22%, the cyclohexanol selectivity was 41.62%, the cyclohexanone selectivity was 47.89%, the cyclohexyl hydroperoxide selectivity was 1.14%, the adipic acid selectivity was 6.17%, and the glutaric acid selectivity was 3.18%.

[0141] Embodiment 53

[0142] In a 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0100 g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50-700-2.0 was dispersed in 16.8320g (200mmol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 24.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 6.53%, the cyclohexanol selectivity was 40.85%, the cyclohexanone selectivity was 48.03%, the cyclohexyl hydroperoxide selectivity was 1.84%, the adipic acid selectivity was 6.24%, and the glutaric acid selectivity was 3.81%.

[0143] Example 54 (Comparative Experiment)

[0144] In a 100mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060g chitosan was dispersed in 16.8320g (200mmol) cyclohexane, the autoclave was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 0.09%, the cyclohexanol selectivity was 11.03%, the cyclohexanone selectivity was 28.62%, the cyclohexyl hydroperoxide selectivity was 60.35%, and the production of adipic acid and glutaric acid was not detected.

[0145] Example 55 (Comparative Experiment)

[0146] In a 100mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060g of anhydrous cobalt acetate was dispersed in 16.8320g (200mmol) of cyclohexane, the autoclave was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 3.59%, the cyclohexanol selectivity was 27.79%, the cyclohexanone selectivity was 19.74%, the cyclohexyl hydroperoxide selectivity was 49.51%, the adipic acid selectivity was 2.67%, and the glutaric acid selectivity was 0.29%.

[0147] Example 56 (Comparative Experiment)

[0148] In a 100mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0060g of anhydrous zinc acetate was dispersed in 16.8320g (200mmol) of cyclohexane, the autoclave was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 1.31%, the formation of cyclohexanol was not detected, the cyclohexanone selectivity was 7.67%, the cyclohexyl hydroperoxide selectivity was 92.33%, the formation of adipic acid was not detected, and the formation of glutaric acid was not detected.

[0149] Example 57 (Comparative Experiment)

[0150] In a 100mL stainless steel autoclave with a polytetrafluoroethylene liner, 0.0030g of anhydrous cobalt acetate and 0.0030g of anhydrous zinc acetate were dispersed in 16.8320g (200mmol) of cyclohexane, the autoclave was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 1.3115g (5.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide was reduced by stirring at room temperature for 30min. The reaction mixture was fixed to 100mL with acetone as solvent. 10mL of the obtained solution was transferred and analyzed by gas chromatography with toluene as internal standard; 10mL of the obtained solution was transferred and analyzed by liquid chromatography with benzoic acid as internal standard. The cyclohexane conversion rate was 2.52%, the cyclohexanol selectivity was 18.52%, the cyclohexanone selectivity was 10.03%, the cyclohexyl hydroperoxide selectivity was 70.19%, the adipic acid selectivity was 1.26%, and the production of glutaric acid was not detected.

[0151] Example 58 (Enlargement Experiment)

[0152] In a 1L stainless steel autoclave with a polytetrafluoroethylene liner, 0.0600g of Co(II) and Zn(II) bimetallic doped carbon material C 4:0.50:0.50 -700-2.0 was dispersed in 168.3200g (2.0mol) of cyclohexane, the reactor was sealed, the temperature was raised to 120°C with stirring, and oxygen was introduced to 1.00MPa. The reaction was stirred at 120°C, 1.00MPa oxygen pressure, and 800rpm for 8.0h. After the reaction was completed, ice water was cooled to room temperature, 131.15g (500.00mmol) of triphenylphosphine (PPh3) was added to the reaction mixture, and the peroxide generated was reduced by stirring at room temperature for 50min. Distillation was performed to recover 132.68g of cyclohexane with a conversion rate of 6.78%; vacuum distillation was performed to obtain 5.32g of cyclohexanol with a selectivity of 43.32%, 6.31g of cyclohexanone with a selectivity of 49.01%, and recrystallization from ethyl acetate was performed to obtain 0.28g of adipic acid with a selectivity of 2.74%, and 0.032g of glutaric acid with a selectivity of 0.40%.

Claims

1. Application of a Co(II) and Zn(II) bimetallic doped carbon material in the catalytic oxidation of cycloalkanes to synthesize cycloalkanols and cycloalkanones, wherein the Co(II) and Zn(II) bimetallic doped carbon material is prepared by the following method: The chitosan is dispersed in a mixed aqueous solution of a Co(II) element donor and a Zn(II) element donor, stirred at 0-80°C for 1-20 hours, then filtered, washed with water, dried, carbonized at 400-800°C under a N2 atmosphere for 1-10 hours, cooled to room temperature, stirred and washed with a 0.5-10 mol / L hydrochloric acid aqueous solution for 1-10 hours, filtered, washed with water until the pH value is 3-8, and vacuum dried to obtain a Co(II) and Zn(II) bimetallic doped carbon material.

2. The use according to claim 1, characterized in that In the preparation method of Co(II) and Zn(II) bimetallic doped carbon material, the Co(II) element donor is one or a mixture of any proportion of two or more of Co(CH3COO)2, Co(NO2)2, CoSO4, CoCl2 and their hydrates.

3. The use according to claim 1, characterized in that In the preparation method of Co(II) and Zn(II) bimetallic doped carbon material, the Zn(II) element donor is one or a mixture of any proportion of two or more of Zn(CH3COO)2, Zn(NO2)2, ZnSO4, ZnCl2 and their hydrates.

4. The use according to claim 1, characterized in that In the preparation method of Co(II) and Zn(II) bimetallic doped carbon material, the ratio of the amount of glucosamine unit substance in the chitosan to the total amount of Co(II) and Zn(II) substances is 4:0.1-2.

5. The use according to claim 1, characterized in that In the preparation method of Co(II) and Zn(II) bimetallic doped carbon material, the molar ratio of the Co(II) and Zn(II) substances is 1:0.1-2.

6. The use according to claim 1, characterized in that The method of application is: The Co(II) and Zn(II) bimetallic doped carbon materials are dispersed in cycloalkane, the reaction system is sealed, the temperature is raised to 80-160°C under stirring, an oxidant is introduced to 0.1-2MPa, the set temperature and pressure are maintained, the reaction is stirred for 2-24h, and the reaction solution is then post-treated to obtain oxidation products cycloalkyl alcohol and cycloalkyl ketone; The cycloalkane is one or a mixture of any proportion of two or more of cyclopentane, cyclohexane, cycloheptane, cyclooctane, cyclononane, cyclodecane and cyclododecane; The oxidant is oxygen, air or a mixture of the two in any proportion.

7. The use according to claim 6, characterized in that The mass dosage of the Co(II) and Zn(II) bimetallic doped carbon material is 0.01 to 10 g / 100 mol based on the amount of cycloalkane.

Citation Information

Patent Citations

  • Cobalt-nitrogen co-doped porous carbon material catalyst as well as preparation method and application thereof

    CN111408392A